2004
DOI: 10.3354/dao061023
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of Sp serotype strains of infectious pancreatic necrosis virus exhibiting differences in virulence

Abstract: Infectious pancreatic necrosis virus (IPNV), a prototype virus of the family Birnaviridae, exhibits a high degree of antigenic variability, pathogenicity and virulence in salmonid species. The Genomic Segment A encodes all the structural (VP2 and VP3) and nonstructural (NS) proteins, whereas Segment B encodes the viral RNA-dependent RNA polymerase (VP1). We tested 3 different IPNV isolates (Sp103, Sp116 and Sp122) isolated during field outbreaks in Norway for their ability to cause mortality in fry and post-sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
108
3
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(118 citation statements)
references
References 27 publications
5
108
3
2
Order By: Relevance
“…Several studies (Bruslind & Reno 2000, Santi et al 2004, Shivappa et al 2004) have reported the presence of threonine and alanine at positions 217 and 221 of virulent strains, whereas low virulent strains have a proline and alanine at the same residues. As seen in Fig.…”
Section: Phylogenetic Analysismentioning
confidence: 99%
“…Several studies (Bruslind & Reno 2000, Santi et al 2004, Shivappa et al 2004) have reported the presence of threonine and alanine at positions 217 and 221 of virulent strains, whereas low virulent strains have a proline and alanine at the same residues. As seen in Fig.…”
Section: Phylogenetic Analysismentioning
confidence: 99%
“…Firstly, viral genomic RNA was isolated from purified virus as described previously [28]. The genomic RNA was reverse-transcribed using a random primer, and the resulting cDNAs were amplified by PCR with six specific primer pairs A1F/A1R, A2F/A2R, A3F/A3R, B1F/ B1R, B2F/B2R and B3F/B3R (Table 1) for obtaining the coding regions of segments A and B.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…3) [3,6,7,28,29,32]. The genomic segments A and B of POBV were analyzed as follows: 497 motifs) in addition to the two primary cleavage sites at the pVP2-VP4 and VP4-VP3 junctions (Fig.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on this sequence, TAB98 was found to cluster within Genogroup 5 along with New Zealand aquabirnaviruses that had been isolated from healthy Chinook salmon Oncorhynchus tshawtscha. Genogroup 5 consists of isolates from diverse geographical and host ranges such as pathogenic IPNV Sp116 isolated from Atlantic salmon in Norway (Shivappa et al 2004).…”
Section: Introductionmentioning
confidence: 99%